Factor Associated With The Incidence Of Choronic Energy Deficiency Pregnant Mothers In The Health Office Area Of Pagar Alam City In 2024 - Anggraini, Nova; Retni, Retni; Darmawansyah, Darmawansyah; Wulandari, Wulandari; Habibi, Julius (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Intoduction: Chronic Energy Deficiency (CED) is a condition where a person's nutritional status is poor due to inadequate consumption of food sources of energy that contain macro- nutrients. There are 9 community health centers (Puskesmas) spread across all sub-districts in Pagar Alam City. From the preliminary survey data obtained in 2024, the number of CED cases in Pagar Alam City is 64 cases. The highest number is in Sidorejo, with 19 cases, while the lowest is at Gunung Dempo Health Center, with 1 case. The general objective of this study is to identify the factors associated with the incidence of Chronic Energy Deficiency in pregnant mothers in the Health Office area of Pagar Alam City in 2024. Method: The research design used is cross-sectional. The population in this study consists of all pregnant mothers who underwent Mid-Upper Arm Circumference (MUAC) measurement in the working area of Sidorejo health center, totaling 588 pregnant mothers. The sample size in this study is 57 pregnant mothers, selected using accidental sampling techniques. The results are presented in univariate and bivariate analyses with chi-square tests at α 5%. Result and Discussion: The results show a significant relationship between parity and the incidence of CED in the working area of Sidorejo health center in 2024 with p=(0.008). There is a significant relationship between maternal knowledge and the incidence of CED in the working area of Sidorejo health center in 2024 with p=(0.019). There is a significant relationship between maternal dietary diversity and the incidence of CED in the working area of Sidorejo health center in 2024 with p=(0.003). There is a significant relationship between maternal income and the incidence of CED in the working area of Sidorejo health center in 2024 with p=(0.012).Conclusion: It is recommended that the results of this study can serve as additional data for the community health center to evaluate the improvement of maternal and child programs, especially for pregnant mothers.